2016
DOI: 10.21873/anticanres.11268
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Non-stented Pancreaticojejunostomy in Pancreaticoduodenectomy for Patients with Soft Pancreas

Abstract: Since pancreatic duct stenting in pancreaticojejunal anastomosis for patients with soft pancreas did not reduce pancreatic fistula after pancreaticoduodenectomy, non-stented pancreaticojejunostomy for soft pancreas seems safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…After dissection of the bile duct, the stump was clamped to avoid spillage of bile juice. Pancreatic texture was assessed intraoperatively by palpation, as described in a previous study 10) . Pancreaticojejunostomy was performed in all patients using twolayer ducttomucosa anastomosis ; the modified -Kakita method 11) with external drainage of the pancreatic duct by a stent.…”
Section: Technique Of Pancreaticoduodenectomy and Perioperative Managmentioning
confidence: 99%
“…After dissection of the bile duct, the stump was clamped to avoid spillage of bile juice. Pancreatic texture was assessed intraoperatively by palpation, as described in a previous study 10) . Pancreaticojejunostomy was performed in all patients using twolayer ducttomucosa anastomosis ; the modified -Kakita method 11) with external drainage of the pancreatic duct by a stent.…”
Section: Technique Of Pancreaticoduodenectomy and Perioperative Managmentioning
confidence: 99%
“…For interest, we performed a pooled analysis of individual studies used in the three meta-analyses of contention, with the addition of Kawaii et al's findings. [1][2][3][4][5][6][7][8][9][10][11][12] This did not overturn the overall conclusion as anticipated by the authors (odds ratio [OR] 0.92, 95% confidence interval [CI] 0.56-1.53, p = 0.75) (Figure 1). Importantly, it was not possible to differentiate between Grade B and Grade C postoperative pancreatic fistula (POPF), which was the insight offered by Jiang et al Their meta-analysis reported a significantly lower rate of Grade C POPF with the use of an external versus internal stent (OR 0.58, 95% CI 0.35-0.96).…”
mentioning
confidence: 78%
“…However, recent studies performed worldwide have revealed that the absence of a pancreatic duct stent is safe and reliable and has no effect on the development of pancreatic fistula. [15][16][17] One randomized controlled study showed that the incidence of postoperative pancreatic fistula did not increase and that no statistically significant difference was present when pancreaticojejunostomy without a pancreatic stenting tube was performed compared with a control group. Other complications such as delayed gastric emptying, abdominal infection, bleeding, and perioperative mortality were not significantly different.…”
Section: Discussionmentioning
confidence: 99%